Adaptation and validation of the Safety Attitude Questionnaire SAQ) in Malaysian healthcare setting - Harris Shah Abd Hamid,; Che Suriya Che Kar,; Nor Shuhada Murad @ Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Safety culture has been shown to be related to patient outcomes and Safety Attitude Questionnaire (SAQ) is one of the measures of safety culture that has good psychometric properties. The present study attempts to adapt the short version of the Generic SAQ for use in Malaysian healthcare setting. The process of adaptation included forward translation and backward translation method, followed by content validity analysis by seven subject matter experts. All 36 items of the SAQ was retained for the field test. The Malaysian SAQ (MSAQ) was distributed to 400 healthcare workers in a hospital in Kuala Lumpur. There were 126 returned and usable questionnaires (31.5% return rate). The internal consistency indices of the MSAQ is acceptable but two items were revised due to low corrected item-total correlation. The revised MSAQ and the Barriers to Medication Administration Error Reporting scale was administered to nurses (n=175, with 76.1% response rate) of two public hospitals in East Peninsula of Malaysia. Internal consistency of the dimensions improved to .71 to .91. Dimensions of MSAQ correlated negatively with the barriers to error reporting, providing evidence of convergent validity. Thus, the revised MSAQ is suggested to be used for research and interventions in Malaysian healthcare organizations.